1998
DOI: 10.1001/jama.280.11.969
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Outcome After Radical Prostatectomy, External Beam Radiation Therapy, or Interstitial Radiation Therapy for Clinically Localized Prostate Cancer

Abstract: Context.-Interstitial radiation (implant) therapy is used to treat clinically localized adenocarcinoma of the prostate, but how it compares with other treatments is not known. Objective.-To estimate control of prostate-specific antigen (PSA) after radical prostatectomy (RP), external beam radiation (RT), or implant with or without neoadjuvant androgen deprivation therapy in patients with clinically localized prostate cancer. Design.-Retrospective cohort study of outcome data compared using Cox regression multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
1,370
3
12

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 3,922 publications
(1,449 citation statements)
references
References 26 publications
12
1,370
3
12
Order By: Relevance
“…Stage 1 consisted of a GWAS to identify novel SNPs. We restricted our GWAS analysis to patients diagnosed with intermediate to high risk prostate cancer for progression to metastasis defined by the D`Amico criteria 8 of prostate cancer risk in order to maximize the probability of finding clinically significant SNPs (rather than those associated with indolent forms of prostate cancer). Stage 2 consisted of a replication study among a separate cohort to determine whether the SNPs from Stage 1 could predict aggressive forms of prostate cancer among a prostate biopsy screening cohort who underwent a prostate biopsy.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Stage 1 consisted of a GWAS to identify novel SNPs. We restricted our GWAS analysis to patients diagnosed with intermediate to high risk prostate cancer for progression to metastasis defined by the D`Amico criteria 8 of prostate cancer risk in order to maximize the probability of finding clinically significant SNPs (rather than those associated with indolent forms of prostate cancer). Stage 2 consisted of a replication study among a separate cohort to determine whether the SNPs from Stage 1 could predict aggressive forms of prostate cancer among a prostate biopsy screening cohort who underwent a prostate biopsy.…”
Section: Methodsmentioning
confidence: 99%
“…In the first stage, 316 cases and 229 controls were genotyped using the Affymetrix 500K SNP array (443,816 SNPs). Cases were patients with aggressive forms of prostate cancer using the established D'Amico classification criteria, 8 and controls were biopsy proven normal patients. In the second stage, we genotyped positive SNPs found from stage 1 among 3439 patients who underwent prostate biopsy for prostate cancer screening.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of multicenter studies 5 , 6 , 7 , 8 have shown that brachytherapy delivered as monotherapy or concurrently with external beam radiotherapy yields biochemical control rates similar to other techniques, while showing the lowest rates of long‐term complications to the organs at risk (OAR) (9) . High‐dose‐rate (HDR) brachytherapy, performed with remote afterloaders, has also the additional advantage of potentially allowing dose escalation (10) without increasing considerably OAR toxicities or treatment times.…”
Section: Introductionmentioning
confidence: 99%
“…Given the wide use of PSA as a component of risk group stratification schemas,17, 18 we further analyzed the impact of PSA value corrections on the recurrence risk categorization of patients with prostate cancer. Comparison of PSA values before and after corrections identified 418 patients (0.83% of the study cohort) who potentially could have been placed in a lower risk category before PSA corrections.…”
Section: Discussionmentioning
confidence: 99%